Triazine-pyridine chemistry for protein labelling on tyrosine. Issue 50 (1st June 2022) - Jiang, Hongfei; Zhang, Qing; Zhang, Yue; Feng, Huxin; Jiang, Hao; Pu, Fan; Yu, Rilei; Zhong, Zheng; Wang, Chaoming; Fung, Yi Man Eva; Blasco, Pilar; Li, Yongxin; et al.
Abstract : Herein, we discover the new reactivity of the 1, 3, 5-triazine moiety reacting with a phenol group and report the development of biocompatible and catalyst-free triazine-pyridine chemistry (TPC) for tyrosine labelling under physiological conditions and profiling in the whole proteome. Abstract : Herein, we discover the new reactivity of the 1, 3, 5-triazine moiety reacting with a phenol group and report the development of biocompatible and catalyst-free triazine-pyridine chemistry (TPC) for tyrosine labelling under physiological conditions and profiling in the whole proteome. TPC exhibited high tyrosine chemoselectivity in biological systems after cysteine blocking, displayed potential in tyrosine-guided protein labelling, and had bio-compatibility in live cells.